2023
DOI: 10.3389/fmolb.2023.1125922
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of Rubisco activase: Dynamic assembly and Rubisco remodeling

Abstract: Ribulose-1,5-bisphosphate (RuBP) carboxylase-oxygenase (Rubisco) enzyme is the limiting step of photosynthetic carbon fixation, and its activation is regulated by its co-evolved chaperone, Rubisco activase (Rca). Rca removes the intrinsic sugar phosphate inhibitors occupying the Rubisco active site, allowing RuBP to split into two 3-phosphoglycerate (3PGA) molecules. This review summarizes the evolution, structure, and function of Rca and describes the recent findings regarding the mechanistic model of Rubisco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…In C3 plants, glucose is primarily biosynthesized through the Calvin cycle. A crucial step in this process is the formation of glycerate-3-phosphate (3PGA) through the action of 1,5-bisphosphate ribulose carboxylase using CO 2 [28]. Rubiscos, which are photosynthetic CO 2 -fixing enzymes, are activated by Rubisco activase (Rcas).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C3 plants, glucose is primarily biosynthesized through the Calvin cycle. A crucial step in this process is the formation of glycerate-3-phosphate (3PGA) through the action of 1,5-bisphosphate ribulose carboxylase using CO 2 [28]. Rubiscos, which are photosynthetic CO 2 -fixing enzymes, are activated by Rubisco activase (Rcas).…”
Section: Discussionmentioning
confidence: 99%
“…NO plays a role in both abscisic acid (ABA)-and Ca 2+ -mediated stomatal closure and is located downstream of ROS, an important participant in the stomatal closure process [24,25]. In A. thaliana, ROS are mainly produced by NADPH oxidase and peroxidase at the plasma membrane [26,27], while NO is mainly produced by nitrate reductase (NR) and NOA1 and induces stomatal closure [28].…”
Section: Introductionmentioning
confidence: 99%
“…The stability in carboxylation efficiency observed in the GM plants under the three collection stages in both irrigation treatments could potentially be linked to enhanced protection against the degradation of Rubisco (ribulose-1,5-bisphosphate carboxylase/oxygenase). Another probable reason was that ribulose activase, the enzyme that regulates Rubisco activation [39], was the most expressed enzyme identified via RNA-seq, with the GM plants under water deficit having 9% more transcripts of this enzyme than the NGM plants under the same irrigation conditions and 18% more transcripts than the NGM plants in the control treatment. Furthermore, the elevated protection against the degradation of this enzyme after re-irrigation in the GM plants may have contributed to a better cellular redox balance, thereby creating a more favorable cellular environment for its preservation and activity.…”
Section: Discussionmentioning
confidence: 99%
“…The stability in carboxylation efficiency observed in GM plants at the three collect stages, in both irrigation treatments, could potentially be linked to enhanced protection against the degradation of Rubisco (ribulose-1,5-bisphosphate carboxylase/oxygenase). Another probable reason was that ribulose activase, the enzyme that regulates Rubisco activation (Waheeda et al, 2023), was the most expressed enzyme identified by RNAseq, with GM plants under water deficit having 9% more transcripts of this enzyme than plants NGM in the same irrigation condition, and 18% more than the NGM plants in the control treatment. Furthermore, the elevated protection against the degradation of this enzyme after re-irrigation in GM plants might have contributed to a better cellular redox balance, thereby creating a a more favorable cellular environment for its preservation and activity.…”
Section: Discussionmentioning
confidence: 99%